Analisis Modal Kerja pada Industri Telekomunikasi di Indonesia - Mutiara Lusiana Annisa; Ruth Samantha Hamzah; Yobi Nagoya Pratiwi (Politeknik Ganesha Medan, 2022)
Working capital is an important aspect of company expenditure. Incapability to maintain a satisfactory level of working capital leads to higher possibility of default. The analysis of sources and uses of working capital is substantial for managers in predicting the usage and spending of efficient working capital. This study purposes to examine the reports on sources and use of working capital of telecommunication companies listed on the Indonesian stock exchange circa 2019 and 2020. Further, we collected six companies as samples, therefore there were 12 sample observations. Quantitative descriptive is used as the method and the secondary data was obtained from the financial reports. The results show that 33.3% of telecommunications companies use working capital optimally, meanwhile the remaining 66.7% have not been efficient in managing their working capital. Companies that are efficient in the use of working capital are PT Jasnita Telekomindo Tbk (JAST) and PT Telkom Indonesia Tbk (TLKM).